Heat insulation ceramic fiber board and preparation method thereof
By using multi-grade aluminum silicate fiber mixed cotton and other high-performance raw materials, combined with vacuum molding and drying processes, the insulation ceramic fiberboard with high strength, long service life, low thermal conductivity and good thermal insulation performance were prepared, and the current solution was solved There are shortcomings in strength and thermal insulation properties of ceramic fiberboards.
Patent Information
- Application Number
- CN202411612952.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing ceramic fiberboard has shortcomings in strength, service life, thermal conductivity and thermal insulation performance, and it is difficult to meet the thermal insulation and fire resistance requirements of high-temperature equipment.
The heat-insulated ceramic fiber board is prepared through vacuum molding and drying processes such as multi-grade aluminum silicate fiber mixed cotton, zirconium oxide fiber, alkaline silicon sol, aqueous resin dispersant, alumina fine powder and high-temperature ceramic sand.
It improves the strength and service life of ceramic fiberboard, reduces the thermal conductivity and heating permanent line change rate, enhances thermal insulation performance and fire resistance, and is suitable for high-temperature environments.
Smart Images

Figure BDA0005131380300000051 
Figure BDA0005131380300000052 
Figure BDA0005131380300000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a heat-insulating ceramic fiberboard and a preparation method thereof. Background Art
[0002] Ceramic fiberboard has good mechanical properties and wind erosion resistance, stable high temperature performance, and is often used as a thermal insulation material for high temperature equipment. It can be used for the lining of various high temperature resistance furnaces, the repair of gaps in industrial kilns, and sealing gaskets when connecting high temperature components. Some high temperature furnaces require thermal insulation materials with a certain strength. Vermiculite materials, olivine materials, lightweight bricks or lightweight castables are usually used as thermal insulation linings. The thermal conductivity of these thermal insulation materials is about 2 to 3 times that of fiber materials, and the thermal insulation performance is poor. However, ceramic fiberboards with better thermal insulation effects generally have lower strength, so the preparation of a ceramic fiberboard with good thermal insulation performance and high strength can meet the requirements of use and energy conservation and emission reduction.
[0003] At present, ceramic fiberboard is usually prepared by wet process, in which short or broken ceramic fiber cotton is mixed with binder, dispersant, filler, etc., and water or sol is added to prepare refractory fiber slurry. The slurry is formed into fiberboard blank by vacuum filtration, and the blank is then dried and sanded to make refractory fiberboard. The ceramic fiberboard products prepared by this process have the problems of low strength, high heating shrinkage and thermal conductivity, poor material structure uniformity, fast fiber pulverization and short service life.
[0004] Patent CN214873280U provides a highly efficient thermal insulation aluminum silicate refractory fiberboard, comprising a first fireproof layer of asbestos board, a glass fiber bidirectional grid reinforcement layer on the first fireproof layer, a second fireproof layer of refractory fiber on the upper surface of the reinforcement layer, a sound insulation layer on the outside of the second fireproof layer, an aluminum silicate coating insulation layer on the outside of the sound insulation layer, a basic fiberboard layer on the outside of the insulation board, and a polyurethane coating waterproof layer on the outside of the basic fiberboard layer. When a fire occurs in the installed product, the fiberboard is not easy to collapse and disperse in the fire, and the double-layer fireproof measures are implemented to make the product better fireproof. The main problem with this highly efficient thermal insulation aluminum silicate refractory fiberboard is that asbestos is a strong carcinogen and is banned by various countries, and the board is a multi-layer structure composite material with a complex production process.
[0005] Patent CN1563578A provides a ceramic fiberboard and its production process, which is made of multiple layers of ceramic fiber paper stacked and pressed, with a binder layer between each two layers of paper, and its production process includes semi-continuous production method and continuous method. The ceramic fiber laminate produced by this patent has high density, strong tensile and impact resistance, good friction resistance, and certain flexibility, but because the thickness of the fiber paper is 0.2-1.0mm and the thickness of the binder layer is 0.5-3.0mm, its production process is more suitable for producing fiberboards with smaller thickness requirements, and the produced fiberboard may be delaminated during use.
[0006] Patent CN112723867A provides a plastic ceramic fiber product, which is wet at room temperature and becomes a fixed dry state after heat drying during use. It is used for thermal insulation of special-shaped parts. It is easy to install and has good anti-scouring ability, solving the problems of difficult installation of refractory fiber products in special-shaped parts and poor thermal insulation effect. The problem with this plastic ceramic fiber product is that the storage and transportation requirements of wet products are high. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a thermal insulation ceramic fiberboard and a preparation method thereof in view of the deficiencies in the prior art. The thermal insulation ceramic fiberboard provided by the present invention has high strength, long service life, low thermal conductivity and good thermal insulation performance.
[0008] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0009] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 96-114 parts of aluminum silicate fiber mixed cotton, 4-6 parts of zirconium oxide fiber, 9-12 parts of alkaline silica sol, 12-15 parts of water-based resin dispersant, 8-10 parts of aluminum oxide fine powder, and 5-8 parts of high-temperature ceramsite sand; wherein the aluminum silicate fiber mixed cotton is a mixture of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers.
[0010] In the above scheme, the mass ratio of the aluminum silicate fiber raw cotton, the aluminum silicate fiber crushed cotton and the aluminum silicate short fiber in the aluminum silicate fiber mixed cotton is 1:(4-8):(1-5); the average diameter of the aluminum silicate fiber mixed cotton is 4.1-4.5 μm; the main chemical composition of the aluminum silicate fiber mixed cotton is: Al2O3 42%-48%, SiO2 45%-55%, Fe2O3 0.3%-0.5%, K2O 0.10%-0.15%, Na2O 0.05%-0.08%. By mixing the multi-graded aluminum silicate fiber materials, the long and short fibers are interlaced with each other, the strength of the thermal insulation ceramic fiberboard is enhanced and its thermal conductivity is reduced.
[0011] In the above scheme, the average length of the aluminum silicate fiber raw cotton is ≥10cm; the aluminum silicate fiber crushed cotton is made by crushing the aluminum silicate fiber raw cotton with a fiber crusher, and the bulk density is 50-65kg / m 3 , the average length is 0.4 to 4.8 cm; the bulk density of the aluminum silicate short fibers is 280 to 320 kg / m 3 , the average length is 0.2~5mm.
[0012] In the above scheme, the ZrO2 content in the zirconia fiber is ≥99%, the average diameter is 4.5-6.5 μm, the operating temperature is 1600-2200°C, and the thermal conductivity is 0.05-0.28 W / (m·k). Zirconia fiber is used to increase the operating temperature, increase the strength of the thermal insulation ceramic fiberboard, and reduce the pulverization of the thermal insulation ceramic fiberboard.
[0013] In the above scheme, the solid content of the alkaline silica sol is 20% to 25%, the pH value is 9 to 10, the viscosity is 7.5 to 7.8 mPa·s, and the average particle size is 8 to 9 nm. The alkaline silica sol used has good temperature resistance and high bonding strength, and can make the fiber and high-temperature ceramsite sand produce a hard spatial structure after drying, while increasing the air permeability and improving the high temperature resistance strength.
[0014] In the above scheme, the solid content of the aqueous resin dispersant is 49% to 51%, and the pH value is 7 to 9. The aqueous resin dispersant reduces the flocculation of cotton pulp during the preparation process through steric stabilization, and effectively wets and disperses the raw materials used in the preparation of thermal insulation ceramic fiberboard, so that they can be evenly and stably dispersed in water.
[0015] In the above scheme, the particle size of the alumina fine powder is 1000 mesh; the alumina fine powder used flows and disperses during the vacuum forming process and is evenly distributed in the entire fiberboard, which can improve the overall strength and heat resistance.
[0016] In the above scheme, the Al2O3 content in the high-temperature ceramsite sand is ≥30%, and the particle size is 0.068-0.208mm; the high-temperature ceramsite sand used has high refractoriness and low expansion rate, and can be well applied to high-temperature environments. When working at high temperatures, it will not be incompatible with the thermal expansion rate of other raw materials in the insulating ceramic fiberboard, causing deformation of the fiberboard and reducing the service life of the fiberboard. At the same time, its higher strength can improve the compressive strength of the fiberboard.
[0017] The present invention also provides a method for preparing the above-mentioned thermal insulation ceramic fiberboard, comprising the following steps:
[0018] Weigh various raw materials, add water into a pulping machine, and then add the aluminum silicate fiber mixed cotton, the zirconium oxide fiber, and the high-temperature ceramsite sand in sequence, stir for 5 minutes, then add the alumina fine powder, the alkaline silica sol, and the aqueous resin dispersant in sequence, and continue stirring for 3 minutes to make cotton pulp; use a vacuum forming machine to make the obtained cotton pulp into a slab, dry the slab to constant weight, and grind it to obtain the insulating ceramic fiberboard.
[0019] In the above scheme, the amount of water used can make the materials mixed evenly.
[0020] In the above scheme, the drying temperature is 110°C±5°C.
[0021] In the present invention, the aluminum silicate fiber blended cotton is composed of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers. The length of the aluminum silicate fiber raw cotton is relatively uniform, with an average length of ≥10 cm, so only using the aluminum silicate fiber raw cotton will result in poor dispersion during the preparation process, and the fiber gap of the finished product is relatively large; while the average length of the aluminum silicate fiber crushed cotton is 0.4-4.8 cm, and the average length of the aluminum silicate short fibers is 0.2-5 mm, and the dispersion will be better during the mixing process. The finished product fiber gap is also smaller when the aluminum silicate fiber blended cotton composed of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers is used in the preparation process. The aluminum silicate fiber blended cotton used has a high content of the main chemical components Al2O3 and SiO2, and has good high temperature resistance. The zirconia fiber used is a lightweight polycrystalline fiber material with excellent heat-resistant and heat-insulating properties. Among all metal oxide fiber refractory materials, it has the lowest thermal conductivity, the best heat-insulating properties, and stable high-temperature performance, non-volatile, and pollution-free. Therefore, the use of zirconia fiber can improve the overall performance of thermal insulation ceramic fiberboard. Multi-graded aluminum silicate fiber mixed cotton and zirconia fiber form a fiber skeleton with smaller gaps during the preparation process. Alumina fine powder with a particle size of 1000 mesh is used as an additive. It flows and disperses during the vacuum forming process, and the particles are filled more evenly. The fine powder is scattered in the gap of the fiber skeleton and gradually evolves into a coating structure with the refractory fiber. The combination with the fiber skeleton is tighter, and the heat resistance of the whole material is gradually increased. High-temperature ceramsite sand has the characteristics of small size, high refractoriness and low expansion rate. It can block the pores of the sample, reduce the internal heat convection of the sample, increase the thermal resistance of the sample, effectively enhance the refractoriness and strength of the thermal insulation ceramic fiberboard, and can be better used in high-temperature environments.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention provides a thermal insulation ceramic fiberboard and a preparation method thereof. The method adopts multi-graded aluminum silicate fiber mixed cotton as the main raw material, zirconium oxide fiber as the toughening material, alkaline silicon solution and aqueous resin dispersant as the binder, and aluminum oxide fine powder and high-temperature ceramsite sand as additives. The prepared thermal insulation ceramic fiberboard has high strength, low heating permanent linear change rate and thermal conductivity coefficient. Therefore, it has good insulation performance in the service environment, obvious energy-saving and consumption-reducing effect, and greatly improved safety when used in a high-temperature furnace.
[0024] (2) The present invention provides a thermal insulation ceramic fiberboard using alumina fine powder with a particle size of 1000 mesh as an additive, which can be evenly dispersed in the mixed fiber cotton slurry, and the overall distribution of the fiberboard after vacuum forming is more uniform. At the same time, the alumina fine powder is more tightly combined with the graded fiber mixed cotton, thereby improving the thermal stability of the thermal insulation ceramic fiberboard.
[0025] (3) The thermal insulation ceramic fiberboard provided by the present invention uses high-temperature ceramsite sand with an Al2O3 content of ≥30% and a particle size of 0.068-0.208 mm as an additive. Compared with ordinary ceramsite, the high-temperature ceramsite sand has the characteristics of small size, high refractoriness and low expansion rate. It can be well applied to high temperature environments to enhance the refractoriness and strength of the thermal insulation ceramic fiberboard. DETAILED DESCRIPTION
[0026] The technical solution of the present invention will be fully and clearly described below in conjunction with specific embodiments, but the described embodiments are only some embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0027] In a specific embodiment, the aluminum silicate fiber mixed cotton used is a mixture of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers, wherein the mass ratio of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers is 1:8:1; the average diameter of the aluminum silicate fiber mixed cotton is 4.1-4.5 μm; the chemical composition of the aluminum silicate fiber mixed cotton is: Al2O3 42%-48%, SiO2 45%-55%, Fe2O3 0.3%-0.5%, K2O 0.10%-0.15%, Na2O0.05%-0.08%. The average length of the aluminum silicate fiber raw cotton used is ≥10 cm. The aluminum silicate fiber crushed cotton used is made by crushing the aluminum silicate fiber raw cotton with a fiber crusher, and the bulk density is 50-65 kg / m 3 The average length is 0.4-4.8cm. The bulk density of the aluminum silicate short fibers used is 280-320kg / m 3, the average length is 0.2-5mm. The ZrO2 content of the zirconium oxide fiber used is ≥99%, the average diameter is 4.5-6.5μm, the operating temperature is 1600-2200℃, and the thermal conductivity is 0.05-0.28W / (m·K). The particle size of the alumina fine powder used is 1000 mesh. The Al2O3 content in the high-temperature ceramsite sand used is ≥30%, and the particle size is 0.068-0.208mm. The solid content of the alkaline silica sol used is 20%-25%, the pH value is 9-10, the viscosity is 7.5-7.8mPa·s, and the average particle size is 8-9nm. The solid content of the water-based resin dispersant used is 49%-51%, the pH value is 7-9, and it is specifically a water-based acrylic resin dispersant.
[0028] Example 1
[0029] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 96 kg of aluminum silicate fiber mixed cotton, 4 kg of zirconium oxide fiber, 9 kg of alkaline silica sol, 12 kg of water-based resin dispersant, 8 kg of aluminum oxide fine powder, and 5 kg of high-temperature ceramsite sand.
[0030] The preparation method of the above-mentioned thermal insulation ceramic fiberboard is as follows:
[0031] Weigh the raw materials according to the weight of the above raw materials, put them into the pulping machine, add water, then add aluminum silicate fiber mixed cotton, zirconium oxide fiber, high-temperature ceramsite sand in turn, stir for 5 minutes, then add alumina fine powder, alkaline silica sol, water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying equipment and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a thermal insulation ceramic fiberboard.
[0032] The thermal insulation ceramic fiberboard prepared in this example was subjected to relevant performance tests, wherein the physical and chemical indicators of the thermal insulation ceramic fiberboard are shown in the following table:
[0033] Table 1
[0034]
[0035] Example 2
[0036] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 102 kg of aluminum silicate fiber mixed cotton, 5 kg of zirconium oxide fiber, 10 kg of alkaline silica sol, 14 kg of water-based resin dispersant, 9 kg of aluminum oxide fine powder, and 6 kg of high-temperature ceramsite sand.
[0037] The preparation method of the above-mentioned thermal insulation ceramic fiberboard is as follows:
[0038] Weigh the raw materials according to the weight of the above raw materials, put them into the pulping machine, add water, then add aluminum silicate fiber mixed cotton, zirconium oxide fiber, high-temperature ceramsite sand in turn, stir for 5 minutes, then add alumina fine powder, alkaline silica sol, water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying equipment and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a thermal insulation ceramic fiberboard.
[0039] The thermal insulation ceramic fiberboard prepared in this example was subjected to relevant performance tests, wherein the physical and chemical indicators of the thermal insulation ceramic fiberboard are shown in the following table:
[0040] Table 2
[0041]
[0042] Example 3
[0043] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 114 kg of aluminum silicate fiber mixed cotton, 6 kg of zirconium oxide fiber, 12 kg of alkaline silica sol, 15 kg of water-based resin dispersant, 10 kg of aluminum oxide fine powder, and 8 kg of high-temperature ceramsite sand.
[0044] The preparation method of the above-mentioned thermal insulation ceramic fiberboard is as follows:
[0045] Weigh the raw materials according to the weight of the above raw materials, put them into the pulping machine, add water, then add aluminum silicate fiber mixed cotton, zirconium oxide fiber, high-temperature ceramsite sand in turn, stir for 5 minutes, then add alumina fine powder, alkaline silica sol, water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying equipment and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a thermal insulation ceramic fiberboard.
[0046] The thermal insulation ceramic fiberboard prepared in this example was subjected to relevant performance tests, wherein the physical and chemical indicators of the thermal insulation ceramic fiberboard are shown in the following table:
[0047] Table 3
[0048]
[0049] Comparative Example 1
[0050] A ceramic fiberboard comprises the following raw materials in parts by weight: 96 kg of aluminum silicate fiber mixed cotton, 4 kg of zirconium oxide fiber, 9 kg of alkaline silica sol, 12 kg of water-based resin dispersant, 8 kg of aluminum oxide fine powder (200 meshes), and 5 kg of high-temperature ceramsite sand.
[0051] The preparation method of the above-mentioned ceramic fiberboard is as follows:
[0052] Weigh the raw materials according to the weight of the above raw materials, put them into a pulping machine, add water, then add aluminum silicate fiber mixed cotton, zirconium oxide fiber, high-temperature ceramsite sand in turn, stir for 5 minutes, then add alumina fine powder (200 mesh), alkaline silica sol, water-based acrylic resin dispersant in turn, continue stirring for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying equipment and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a ceramic fiberboard.
[0053] The ceramic fiberboard prepared in this comparison was subjected to relevant performance tests, and the physical and chemical indicators of the ceramic fiberboard are shown in the following table:
[0054] Table 4
[0055]
[0056]
[0057] In this comparative example, 200-mesh alumina fine powder was used. Compared with Example 1 using 1000-mesh alumina fine powder, the various properties of the ceramic fiber board prepared in this comparative example were reduced to a certain extent, indicating that the 1000-mesh fine powder filler is easier to be evenly dispersed in the slurry during the preparation process, and the filler distribution in the insulating ceramic fiber board after vacuum forming is more uniform, and the overall heat resistance and stability are enhanced.
[0058] Comparative Example 2
[0059] A ceramic fiberboard comprises the following raw materials in parts by weight: 96 kg of aluminum silicate fiber mixed cotton, 4 kg of zirconium oxide fiber, 9 kg of alkaline silica sol, 12 kg of water-based resin dispersant, 8 kg of aluminum oxide fine powder, and 5 kg of clay particles (with a particle size of 0.075-0.200 mm).
[0060] The preparation method of the above-mentioned ceramic fiberboard is as follows:
[0061] Weigh the raw materials according to the weight of the above raw materials, put them into a pulping machine, add water, then add aluminum silicate fiber mixed cotton, zirconium oxide fiber, clay particles in turn, stir for 5 minutes, then add aluminum oxide fine powder, alkaline silica sol, water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying device and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a ceramic fiberboard.
[0062] The ceramic fiberboard prepared in this comparison was subjected to relevant performance tests, and the physical and chemical indicators of the ceramic fiberboard are shown in the following table:
[0063] Table 5
[0064]
[0065] In this comparative example, clay particles with a particle size similar to that of the high-temperature ceramsite sand in the embodiment are used. Compared with the high-temperature ceramsite sand, the thermal conductivity of the ceramic fiber board prepared in this comparative example is increased. Although the clay particles can also block the pores in the insulating ceramic fiber board, the clay particles themselves do not have pores. While the high-temperature ceramsite sand blocks the pores of the sample, it has micropores itself, and the thermal insulation effect is better.
[0066] Comparative Example 3
[0067] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 96 kg of aluminum silicate fiber wool, 4 kg of zirconium oxide fiber, 9 kg of alkaline silica sol, 12 kg of water-based resin dispersant, 8 kg of aluminum oxide fine powder, and 5 kg of high-temperature ceramsite sand.
[0068] The preparation method of the above-mentioned thermal insulation ceramic fiberboard is as follows:
[0069] Weigh the raw materials according to the weight of the above raw materials, put them into the pulping machine, add water, then add aluminum silicate fiber raw cotton, zirconium oxide fiber, high-temperature ceramsite sand in turn, stir for 5 minutes, then add aluminum oxide fine powder, alkaline silica sol, water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, use a vacuum forming machine to make the obtained cotton pulp into a slab; put the slab into a microwave drying equipment and dry it at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a thermal insulation ceramic fiberboard.
[0070] The thermal insulation ceramic fiberboard prepared in this example was subjected to relevant performance tests, wherein the physical and chemical indicators of the thermal insulation ceramic fiberboard are shown in the following table:
[0071] Table 6
[0072]
[0073] In this comparative example, only aluminum silicate fiber raw cotton is used. Compared with the use of aluminum silicate fiber mixed cotton, the ceramic fiber board prepared in this comparative example forms a fiber skeleton with larger gaps during the preparation process, has a smaller volume density, and has reduced compressive strength.
[0074] Comparative Example 4
[0075] A heat-insulating ceramic fiberboard comprises the following raw materials in parts by mass: 100 kg of aluminum silicate fiber mixed cotton, 0 kg of zirconium oxide fiber, 9 kg of alkaline silica sol, 12 kg of water-based resin dispersant, 8 kg of aluminum oxide fine powder, and 5 kg of high-temperature ceramsite sand.
[0076] The preparation method of the above-mentioned thermal insulation ceramic fiberboard is as follows:
[0077] Weigh the raw materials according to the weight of the above raw materials, put them into the pulping machine, add water, then add aluminum silicate fiber mixed cotton and high-temperature ceramsite sand in turn, stir for 5 minutes, then add alumina fine powder, alkaline silica sol, and water-based acrylic resin dispersant in turn, continue to stir for 3 minutes to make cotton pulp, and use a vacuum forming machine to make the obtained cotton pulp into a slab; the slab is placed in a microwave drying device and dried at a temperature of 110°C to constant weight. Finally, use a sander to polish the surface and side of the obtained fiberboard to make a thermal insulation ceramic fiberboard.
[0078] The thermal insulation ceramic fiberboard prepared in this example was subjected to relevant performance tests, wherein the physical and chemical indicators of the thermal insulation ceramic fiberboard are shown in the following table:
[0079] Table 7
[0080]
[0081] In this comparative example, only aluminum silicate fiber mixed cotton was used. Compared with adding zirconium oxide fiber, the refractoriness of the ceramic fiber board prepared in this comparative example was reduced and the heating permanent line change rate was increased.
[0082] In summary, the present invention provides a thermal insulation ceramic fiber board and a preparation method thereof. The thermal insulation ceramic fiber board provided by the present invention has high strength, long service life, low heating permanent linear change rate and thermal conductivity, and good thermal insulation performance.
[0083] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A thermal insulation ceramic fiberboard, characterized in that: The invention comprises the following raw materials in parts by weight: 96-114 parts of aluminum silicate fiber mixed cotton, 4-6 parts of zirconium oxide fiber, 9-12 parts of alkaline silica sol, 12-15 parts of water-based resin dispersant, 8-10 parts of aluminum oxide fine powder and 5-8 parts of high-temperature ceramsite sand; wherein the aluminum silicate fiber mixed cotton is a mixture of aluminum silicate fiber raw cotton, aluminum silicate fiber crushed cotton and aluminum silicate short fibers.
2. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The mass ratio of the aluminum silicate fiber raw cotton, the aluminum silicate fiber crushed cotton and the aluminum silicate short fiber in the aluminum silicate fiber mixed cotton is 1:(4-8):(1-5); the average diameter of the aluminum silicate fiber mixed cotton is 4.1-4.5 μm; the main chemical composition of the aluminum silicate fiber mixed cotton is: Al2O3 42%-48%, SiO2 45%-55%, Fe2O3 0.3%-0.5%, K2O 0.10%-0.15%, Na2O 0.05%-0.08%.
3. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The average length of the aluminum silicate fiber raw cotton is ≥10cm; the aluminum silicate fiber crushed cotton is made by crushing the aluminum silicate fiber raw cotton with a fiber crusher, and the bulk density is 50-65kg / m 3 , the average length is 0.4 to 4.8 cm; the bulk density of the aluminum silicate short fibers is 280 to 320 kg / m 3 , the average length is 0.2~5mm.
4. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The ZrO2 content in the zirconia fiber is ≥99%; the average diameter of the zirconia fiber is 4.5-6.5 μm, the operating temperature is 1600-2200° C., and the thermal conductivity is 0.05-0.28 W / (m·k).
5. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The Al2O3 content in the high-temperature ceramsite sand is ≥30%, and the particle size is 0.068-0.208 mm.
6. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The alkaline silica sol has a solid content of 20% to 25%, a pH value of 9 to 10, a viscosity of 7.5 to 7.8 mPa·s, and an average particle size of 8 to 9 nm.
7. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The solid content of the aqueous resin dispersant is 49% to 51%, and the pH value is 7 to 9.
8. The thermal insulation ceramic fiberboard according to claim 1, characterized in that: The particle size of the alumina fine powder is 1000 mesh.
9. The method for preparing the thermal insulation ceramic fiberboard according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: weighing various raw materials, adding water into a pulping machine, and then sequentially adding the aluminum silicate fiber mixed cotton, the zirconium oxide fiber, and the high-temperature ceramsite sand, stirring for 5 to 10 minutes, and then sequentially adding the aluminum oxide fine powder, the alkaline silica sol, and the aqueous resin dispersant, and continuing stirring for 3 to 5 minutes to form cotton pulp; using a vacuum forming machine to form the obtained cotton pulp into a slab, drying the slab to a constant weight, and polishing to obtain the thermal insulation ceramic fiberboard.
10. The method for preparing the thermal insulation ceramic fiberboard according to claim 9, characterized in that: The drying temperature is 110°C ± 5°C.
Citation Information
Cited By
Inorganic fiber insulation board based on dry method and preparation method thereof
CN121159223A
Inorganic fiber-based thermal insulation board and preparation method thereof
CN121181324A
Quartz reinforced calcium silicate fiberboard and preparation method thereof
CN122520433A
Composite aluminum silicate fiberboard and method of making same
CN122705256A